A longitudinal study of COVID-19 disclosure stigma and COVID-19 testing hesitancy in the United States. (November 2022) - Dayton, L.; Song, W.; Kaloustian, I.; Eschliman, E.L.; Strickland, J.C.; Latkin, C.
Abstract: Objectives: This study examines the relationship between COVID-19 disclosure stigma and COVID-19 testing hesitancy and assesses their changes between November 2020 and 2021. Study design: This was a longitudinal cohort. Methods: A total of 355 participants completed four study waves between November 2020 and November 2021. Factor analyses and Cronbach's alpha assessed the factor structure and internal consistency of the COVID-19 Disclosure Stigma scale. Paired t -tests and McNemar's Chi-squared test assessed change between the study waves. Multivariable logistic regression models examined the relationship between COVID-19 disclosure stigma and testing hesitancy at four study waves. Results: COVID-19 disclosure stigma declined significantly between the last study waves ( P  = 0.030). The greatest disclosure concern was reporting a positive test to close contacts (range: 19%–21%) followed by disclosure to friends (range: 10%–15%) and family (range: 4%–10%). Over the course of the four study waves, COVID-19 testing hesitancy when symptomatic ranged from 23% to 30%. Older age, female gender, and having received a COVID-19 vaccine were associated with decreased odds of testing hesitancy. Greater COVID-19 disclosure stigma and more conservative political ideology showed a consistent relationship with increased odds of COVID-19 testing hesitancy. Conclusions: Study findings suggest that many people anticipate feeling stigmatized when disclosing positive test results, especially to close contacts. A substantial percentage of study participants reported hesitancy to be tested when symptomatic. This study identifies a need for interventions that normalize COVID-19 testing (e.g. engaging leaders with conservative followings), provide strategies for disclosing positive results, and allow anonymous notification of potential COVID-19 exposure.